BUCKLING OF CIRCULAR PLATES WITH AN INTERNAL ELASTIC RING SUPPORT AND OUTER EDGE RESTRAINED AGAINST TRANSLATION - LOKAVARAPU BHASKARA RAO; CHELLAPILLA KAMESWARA RAO (Journal of Engineering Science and Technology, 2012)
This paper is concerned with the elastic buckling of circular plates with an internal elastic ring support and elastically restrained edge against translation. The classical plate theory is used to derive the governing differential equation for circular plate with internal elastic ring support and flexible edge support system. This work presents the existence of buckling mode switching with respect to the radius of internal elastic ring support. The buckling mode may not be axisymmetric as previously assumed. The plate may buckle in an axisymmetric mode in general, but when the radius of the ring support becomes small, the plate may buckle in an asymmetric mode. The cross-over ring support radius varies from 0.1255 to 0.09371 times the plate radius, depending on the translational stiffness of the elastic restraint at the edges and elastic restraint of the ring support. The optimum radius of the internal elastic ring support is also determined. Extensive data is tabulated so that pertinent conclusions can be arrived at on the influence of translational restraints, Poisson’s ratio, and other boundary conditions on the buckling of uniform isotropic circular plates. The numerical results obtained are in good agreement with the previously published data.